Łydczaność - Gondowicz, Jan (Wydawnictwo Naukowe UAM, 2013)
In Ferdydurke Witold Gombrowicz presented the secret of interpersonal relations by using anatomical metaphors. In this ironic lecture a calf plays as important role as buttocks (stuck to the face) – it is a symbol of seductive youth and, to a considerable degree, of an unaware, but intuitive infantility. This topic is covered in the novel as part of an episode about a fascinating teenage girl Zuta, who is one of most demonic characters in the 20th-century prose. This paper draws attention to the ambiguity of the self-emancipating strategy that Gombrowicz’s hero uses when he discovers this notion and in order to fight against it. A calf, which represents the temptation of modern, sterile and totalitarian sex appeal, refers – as a spiritual, form-shaping power – to the lack of self-confidence that contemporary people conceal, also from themselves. And that is the hidden origin – as Gombrowicz implies – of mass culture’s erotic blackmail.
Calfiness